Obras para contrabaixo com gêneros da música popular brasileira: performance e aspectos pedagógicos. - Lucena, Diuliano Vitor (2017)
This paper addresses interpretative and pedagogical aspects of double bass works within Brazilian popular music genders. The major objective is to update the Brazilian Online Catalog of Erudite Work for Double Bass (RAY, 2005), and discuss interpretative and teaching aspects from the selection of work which presents characteristics of brazilian popular music genders in this collection. The methodology is qualitative and it presents, at first, a discussion of the addressed repertoire. Next, it develops a proposal for pedagogical and interpretation possibilities applicable to the bassist training. The work is organized in three parts: process of catalog update, selection of the work which was debated and discussion about the performance the performance and suggestions for studies of the workpieces. As a result, 81 new workpieces, which were accumulated from 2006 to 2016, were listed and included in the catalog that bear 136 compositions. After this update, the catalog currently bears 222 workpieces, and 81 of these workpieces hold elements of the Brazilian Popular Music Gender. It is concluded with the proposal of a possible pedagogical path in order to study and solve technical problems as articulation (bow stroke and bowing) in repertoire with choro and baião citations, in order to exemplify and suggest how to perform works with citations of MPB genders in concert music.